Spatial distribution pattern of Phytophthora inoculum in cardamom soils - and Y.R. SARMA, R. SUSEELA BHAI* (Indian Phytopathology, 2008)
An experiment was undertaken to study the soil inoculum build up and distribution pattern of Phytophthora in cardamom soils. Two different locations representing high and low disease intensity were selected. The inoculum distribution was studied at three different depths and distance from the plant base. In high disease pressure area, the Phytophthora propagules are present throughout the season at almost all depths and distance studied whereas in low disease pressure area the population level was comparatively low during April-June months at all the depths and distance. The inoculum build up starts during July and the level became comparatively high during December months at 0-5cm distance from the plant base. In the high disease pressure area also inoculum build up was noticed during November -December months. The inoculum distribution was noticed at all the depths irrespective of distance from the plant base. It is observed that the inoculum build up occurs only when there is sufficient moisture in the soil as evidenced from the inoculum level in the low disease pressure area. The pH of the soil was found between 5 and 6 which is a congenial condition for the growth of Phytophthora.